Improving the Activity of Tryptophan Synthetase via a Nucleic Acid Scaffold - Yaping Wang; Xiangyi Wang; Shuhui Niu; Wei Cheng; Xiaoyan Liu; Yong Min; Yimin Qiu; Lixin Ma; Ben Rao; Lei Zhu (Molecules, 2023)
Tryptophan synthetase (TSase), which functions as a tetramer, is a typical enzyme with a substrate channel effect, and shows excellent performance in the production of non-standard amino acids, histamine, and other biological derivatives. Based on previous work, we fused a mutant CE protein (colistin of E. coli, a polypeptide with antibacterial activity) sequence with the sequence of TSase to explore whether its catalytic activity could be enhanced, and we also analyzed whether the addition of a DNA scaffold was a feasible strategy. Here, dCE (CE protein without DNase activity) protein tags were constructed and fused to the TrapA and TrapB subunits of TSase, and the whole cell was used for the catalytic reaction. The results showed that after the dCE protein tag was fused to the TrapB subunit, its whole cell catalytic activity increased by 50%. Next, the two subunits were expressed separately, and the proteins were bound in vitro to ensure equimolar combination between the two subunits. After the dCE label was fused to TrapB, the activity of TSase assembled with TrapA also improved. A series of experiments revealed that the enzyme fused with dCE9 showed higher activity than the wild-type protein. In general, the activity of assembly TSase was optimal when the temperature was 50 °C and the pH was about 9.0. After a long temperature treatment, the enzyme maintained good activity. With the addition of exogenous nucleic acid, the activity of the enzyme increased. The maximum yield was 0.58 g/L, which was almost three times that of the wild-type TSase (0.21 g/L). The recombinant TSase constructed in this study with dCE fusion had the advantages of higher heat resistance and higher activity, and confirmed the feasibility of adding a nucleic acid scaffold, providing a new idea for the improvement of structurally similar enzymes.